Determinan Akademisi Perguruan Tinggi Terhadap Akselerasi Proteksi Internasional Atas Karya Cipta Dalam Hak Kekayaan Intelektual - Ahmad Iffan; Resma Bintani Gustaliza; Febrina Annisa; Hendriko Arizal; Helmi Chandra SY; Sintong Arion Hutapea (Fakultas Hukum Universitas Bangka Belitung, 2025)
The international intellectual property law regime provides a global legal framework for the protection of copyright works; however, its implementation within higher education institutions remains challenging. This study aims to analyze the determinants of university academics’ engagement in copyright registration within the international intellectual property regime and to identify the factors influencing the low participation rate in copyright protection. The study employs a juridical-empirical approach by examining institutional data and internal policy frameworks of the selected higher education institution. The findings reveal that although the number of academic staff with advanced degrees is relatively high, the rate of copyright registration has significantly declined. Determinant factors identified include legality, institutional appreciation, research clustering, administrative obligation, personal branding, and dissemination of IP policy. The study concludes that weak legal awareness and limited institutional policy enforcement are the primary barriers to effective copyright protection. Therefore, strengthening institutional regulations and aligning them with international legal principles are essential strategies to enhance academic participation in copyright registration both nationally and internationally.